2011
DOI: 10.1200/jco.2010.31.0664
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Geriatric Assessment in the Decision-Making Process in Elderly Patients With Cancer: ELCAPA Study

Abstract: Functional status assessed by the ADL score and malnutrition were independently associated with changes in cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
235
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 381 publications
(255 citation statements)
references
References 44 publications
(6 reference statements)
11
235
1
8
Order By: Relevance
“…A systematic assessment aids in staging the aging, thereby discriminating between fit and relatively vulnerable patients (44), and it reveals deficits that are not routinely captured in standard history and examination (8). A multidisciplinary discussion on the basis of the results of a GA can lead to adjustments of initial treatment proposals in elderly patients in the oncology department by either increasing or decreasing the treatment intensity (45,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic assessment aids in staging the aging, thereby discriminating between fit and relatively vulnerable patients (44), and it reveals deficits that are not routinely captured in standard history and examination (8). A multidisciplinary discussion on the basis of the results of a GA can lead to adjustments of initial treatment proposals in elderly patients in the oncology department by either increasing or decreasing the treatment intensity (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Concrete information on impaired domains that could compromise dialysis treatment may facilitate shared decision making with the patient and relatives. In addition, it may reveal treatable conditions that would otherwise be overlooked (4,48), thereby forming a starting point for (preventive) interventions to optimize quality of life, such as physical and ADL impairments and social problems (45,49). Finally, the information derived from a GA may help to estimate adverse outcomes of surgical interventions (50) and other complex interventions (51).…”
Section: Discussionmentioning
confidence: 99%
“…To assess the profile of each individual patient, a multidimensional geriatric assessment (GA) [2,3].The GA produces an inventory of health problems and an assessment of physical, psychosocial, and functional capabilities [4].The GA has proved useful for characterizing health and functional impairments potentially associated with oncological outcomes [2,[5][6][7]. Nevertheless, it requires considerable time and human resources and is actually not required in all patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…CGA is also used to identify patients at increased risk of adverse outcomes and guide management (21). In previous studies, the CGA tool and the frailty index for geriatric cancer patients were shown to provide valuable information through the prediction of complications from chemotherapy and tolerance to treatment (22,23).…”
Section: Discussionmentioning
confidence: 99%